Tuberculosis in Brent. Issue 553 (November 1971) - McNicol, M. W.; Mikhail, J. R.; Sutherland, I.
Abstract : An analysis has been made of the problem of tuberculosis in the Borough of Brent. There have been changes in the population structure, the groups from which cases are drawn and the types of disease. There has been an increase in the incidence of tuberculosis in immigrants of African and Asian origin, with more non-pulmonary disease. Pulmonary disease in these groups has different clinical characteristics from those of disease in natives of the British Isles.